IDENTIFICATION OF EARLY MARKERS FOR PREDICTING THE REALIZATION OF PREECLAMPSIA (European Journal of Interdisciplinary Research and Development, 2025)
Preeclampsia is one of the dangerous complications of pregnancy, significantly increasing maternal and perinatal morbidity and mortality. Effective forecasting of the development of this condition makes it possible to identify the risk in a timely manner and take preventive measures. Modern approaches to forecasting are based on the identification of biomedical and molecular genetic predictors, as well as an assessment of the individual risk of developing preeclampsia.